Landscape gardening as an art - Bayless, Jessie Geneva (My University, 1898)
Introduction: Our first, most endearing, and most sacred associations, are connected with gardens, our most simple and most refined perception of beauty are combined with them. Landscape Gardening, which is an artistic combination of the beautiful in nature and art, is capable of affording us the highest and most intellectual enjoyment to be found in any cares or pleasures belonging to the soil.
Citation: Bayless, Jessie Geneva. Landscape gardening as an art. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Gardens; Landscape Gardening; Nature and Art; Theses; Manuscripts (documents)